THE COMPARISON OF USING SNAKE LADDERS AND SCRABBLE MEDIA TOWARDS VOCABULARY MASTERY OF STUDENTS - Eka Pra Setiawati; Refai - - (Premise: Journal of English Education and Applied Linguistics, 2014)
Vocabulary is an essential component in learning English. It influences four English skills; they are listening, speaking, reading, and writing, for getting a good result in English. In teaching learning process, the teacher often implements the less interesting method, technique, or even media of vocabulary mastery in teaching and learning process which make the students to be bored, inactive, an uniterested in memorizing English vocabulary. Some media can be interested as the solutions in vocabulary mastery, they are Snake Ladders media and Scrabble media.The investigation was undergone by quantitative research. The researcher applied experimental research. This research underwent pre-test post-test control group design. To analyze data, t-test formula is used to measure the result of collected data. From the t-test measurement, it showed that t-test is 3.15 and t-table is 2.66. It means that t-hit > t-table. Based on the collected data, there is different result of using Snake Ladders from Scrabble media toward students’ vocabulary mastery. It was found that the students who are taught by using Snake Ladders resulted significant outcome than those are instructed by Scrabble media. It means that Snake Ladders is effective to improve the students’ vocabulary mastery.